Sunscreen Application, Safety, and Sun Protection: The Evidence. Issue 4 (July 2019) - Li, Heidi; Colantonio, Sophia; Dawson, Andrea; Lin, Xing; Beecker, Jennifer
Recently in Canada, there has been an effort to create consistent messaging about sun safety as there is a lack of up-to-date evidence-based guidelines regarding sun-protection measures. This review aimed to provide updated, evidence-based recommendations on sunscreen application, safety, and sun protection regarding the following topics for which there is clinical uncertainty: physical barriers, sunscreen properties, sunscreen application, and risk-benefit analysis.